2021
DOI: 10.1016/j.esmoop.2021.100077
|View full text |Cite
|
Sign up to set email alerts
|

S-1 and oxaliplatin versus tegafur-uracil and leucovorin as post-operative adjuvant chemotherapy in patients with high-risk stage III colon cancer: updated 5-year survival of the phase III ACTS-CC 02 trial

Abstract: Background: The ACTS-CC 02 trial demonstrated that S-1 plus oxaliplatin (SOX) was not superior to tegafur-uracil and leucovorin (UFT/LV) in terms of disease-free survival (DFS) as adjuvant chemotherapy for high-risk stage III colon cancer (any T, N2, or positive nodes around the origin of the feeding arteries). We now report the final overall survival (OS) and subgroup analysis according to the pathological stage (TNM 7th edition) for treatment efficacy. Patients and methods: Patients who underwent curative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In the ACTS-CC02 study, S-1 plus oxaliplatin therapy (SOX) was not superior to UFT/LV in terms of OS and disease-free survival (DFS) in patients with high-risk stage III colon cancer of any T, N2, or positive nodes around the origin of the feeding arteries (18,20). SOX was efficacious in patients with T4N2b disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ACTS-CC02 study, S-1 plus oxaliplatin therapy (SOX) was not superior to UFT/LV in terms of OS and disease-free survival (DFS) in patients with high-risk stage III colon cancer of any T, N2, or positive nodes around the origin of the feeding arteries (18,20). SOX was efficacious in patients with T4N2b disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, oxaliplatin-combined regimen was not superior to fluoropyrimidines in our real-world data even in the T4 population with or without N2b. The mean relative dose intensity (RDI) was 83.1% for UFT, 74.9% for S-1 and 73.6% for oxaliplatin in SOX in ACTS-CC02 (20). The RDI of S-1 in SOX therapy was similar to the 76.5% of RDI with S-1 monotherapy and 76.0% with UFT in ACTS-CC study, which showed the non-inferiority of S-1 to UFT/LV for stage III colon cancer (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018 Chinese cancer statistics show that the incidence and mortality rate of colorectal cancer in China occupy two of the top five positions among all malignant tumors, which is a high incidence cancer, and the incidence of colorectal cancer is still on the rise, and the incidence of colorectal cancer in urban population is much higher than the incidence of colorectal cancer in rural population (2,3). The disease can lead to abdominal pain, abdominal lumps and other symptoms, and in serious cases, metastasis may occur, leading to death, which poses a threat to patients' physical and psychological health and life safety (4)(5)(6). At the same time, colon cancer has the characteristics of high incidence and insidious development, so that in most cases, patients only seek medical treatment when they have symptoms in the middle and late stages.…”
Section: Introductionmentioning
confidence: 99%
“…12 The review process (Appendix Fig A1, online only) led to the inclusion of five articles, including eight trials. 3,5,7,13,14 All studies, except for the ADORE study, were randomized phase III trials that tested the efficacy of oxaliplatin-based adjuvant CT in high-risk patients with stage II-III CRC (Appendix Table A1, online only). All studies reported an OS data of 1,985 patients.…”
mentioning
confidence: 99%